A Phase I-II Study of Docetaxel and Atrasentan in Men with Castration-Resistant Metastatic Prostate Cancer - Andrew J. Armstrong; Patricia Creel; James Turnbull; Cassandra N. Moore; Tracy A. Jaffe; Sherri Haley; William P. Petros; Sarah Yenser; Jon P. Gockerman; Darryl J. Sleep; Herbert I. Hurwitz; Daniel J. George (2008)
Abstract Purpose: The primary aims of this phase I-II study were to determine the maximum tolerated dose, dose-limiting toxicity, pharmacokinetics, and preliminary efficacy of the combination of docetaxel and the endothelin A receptor antagonist atrasentan as first-line treatment for men with metastatic castration-resistant prostate cancer. Experimental Design: Patients were treated with docetaxel at doses ranging from 60 to 75 mg/m2 every 21 days, with daily oral atrasentan 10 mg starting on day 3. Patients were treated until evidence of disease progression or unacceptable toxicity. Results: Thirty-one patients were enrolled over three docetaxel dose levels (8 at 60 mg/m2, 19 at 70 mg/m2, and 4 at 75 mg/m2) including dose expansion at 70 mg/m2. The maximum tolerated dose of docetaxel was 70 to 75 mg/m2. Drug-related grade 3-4 toxicities included neutropenia (50-63%) and febrile neutropenia (16-25%); other grade 1-2 toxicities included fatigue, peripheral edema, diarrhea, headache, rhinitis, anorexia, and nausea. Confirmed prostate-specific antigen (PSA) responses were observed in 23% [95% confidence interval (95% CI), 10-41%]; the rate of >30% declines in PSA was 35% (95% CI, 19-55%). Median overall survival was 17.6 months (95% CI, 13.0-23.2) and median progression-free survival was 4.2 months (95% CI, 2.3-5.8). Significant declines in bone alkaline phosphatase and serum N-telopeptides were observed with therapy. Conclusions: The maximum tolerated dose of every-3-week docetaxel with 10 mg atrasentan is 70 to 75 mg/m2. Overall survival and progression-free survival are comparable to that seen with docetaxel and prednisone, whereas the rates of PSA decline are slightly lower than expected. A phase III study of this combination with prednisone has been initiated and is ongoing.